Integrating digital technology in education : school-university-community collaboration - Reardon, R. Martin; Leonard, Jack, 1948- (Current perspectives on school/university/community research., 2019)
"This volume in the Current Perspectives on School/University/Community Research series brings together the perspectives of authors who are deeply committed to the integration of digital technology with teaching and learning. Authors were invited to discuss either a completed project, a work-in-progress, or a theoretical approach which aligned with one of the trends highlighted by the New Media Consortium's NMC/CoSN Horizon Report: 2017 K-12 Edition, or to consider how the confluence of interest and action (Thompson, Martinez, Clinton, & Diaz, 2017) among school-university-community collaborative partners in the digital technology in education space resulted in improved outcomes for all--where "all" is broadly conceived and consists of the primary beneficiaries (the students) as well as the providers of the educational opportunities and various subsets of the community in which the integrative endeavors are enacted. The chapters in this volume are grouped into four sections: Section 1 includes two chapters that focus on computational thinking/coding in the arts (music and visual arts); Section 2 includes three chapters that focus on the instructor in the classroom, preservice teacher preparation, and pedagogy; Section 3 includes four chapters that focus on building the academic proficiency of students; and Section 4 includes two chapters that focus on the design and benefits of school-university-community collaboration"--